THERMODYNAMIC MODELLING OF THE REACTION MUSCOVITE + CORDIERITE → AL2SIO5 + BIOTITE + QUARTZ + H2O: CONSTRAINTS FROM NATURAL ASSEMBLAGES AND IMPLICATIONS FOR THE METAPELITIC PETROGENETIC GRID - Pattison D.R.M.; Spear F.S.; Debuhr C.L.; Cheney J.T.; Guidotti C.V. (My University, 2002)
The reaction muscovite+cordierite→biotite+Al2SiO5 +quartz+H2O is of considerable importance in the low pressure metamorphism of pelitic rocks: (1) its operation is implied in the widespread assemblage Ms + Crd +And± Sil + Bt + Qtz, a common mineral assemblage in contact aureoles and low pressure regional terranes; (2) it is potentially an important equilibrium for pressure estimation in low pressure assemblages lacking garnet; and (3) it has been used to distinguish between clockwise and anticlockwise P–T paths in low pressure metamorphic settings. Experiments and thermodynamic databases provide conflicting constraints on the slope and position of the reaction, with most thermodynamic databases predicting a positive slope for the reaction. Evidence from mineral assemblages and microtextures from a large number of natural prograde sequences, in particular contact aureoles, is most consistent with a negative slope (andalusite and/or sillimanite occurs upgrade of, and may show evidence for replacement of, cordierite). Mineral compositional trends as a function of grade are variable but taken as a whole are more consistent with a negative slope than a positive slope. Thermodynamic modelling of reaction 1 and associated equilibria results in a low pressure metapelitic petrogenetic grid in the system K2O–FeO–MgO–Al2O3–SiO2–H2O (KFMASH) which satisfies most of the natural and experimental constraints. Contouring of the Fe–Mg divariant interval represented by reaction 1 allows for pressure estimation in garnet-absent andalusite+cordierite-bearing schists and hornfelses. The revised topology of reaction 1 allows for improved analysis of P–T paths from mineral assemblage sequences and microtextures in the same rocks.